EFEK ANTIBAKTERI EKSTRAK KULIT BUAH DELIMA (PUNICA GRANATUM) TERHADAP SHIGELLA DYSENTRIAESECARA IN VITRO - Prihantoro, Teguh; Indra, Rasjad; Sumarno, Sumarno (Jurnal Kedokteran Brawijaya, 2006)
Shigella dysentriae is the most common organisms which causes bacillary dysentery in developing countries with high mortality. Pomegranates (Punica granatum) have beenused since a long time ago in folk medicine for several purposes. The antibacterial activity was linked to the presence of major phytocompounds like flavonoids, triterpenes, phenols, and ellagitannin. The aim of this experimental study wasto evaluate the antibacterial effect of Pomegranate’s (Punica Granatum) rind extract against Shigella dysentriae  and to determine the relationship between concentrations of Pomegranate’s rind extract with the growth of Shigella dysentriae in vitro. Antimicrobial effect was determined by tube dilution method. This consists of determination of  Minimum Inhibitory Concentrations (MICs), and Minimum Bactericidal Concentrations (MBCs). The concentrations of Pomegranate’s (Punica Granatum) rind extract were 0.8%, 1%, 1.2%, 1.4%, 1.6%, and 1.8%. At low extract concentration (0.8%)bacterial growth was delayed, while at higher extract concentration (1.8%) bacterial growth was elimanated (ANOVA, p =  0.000, Regression R = -0.901)